SOCIAL WORK SUPERVISION: A QUALITATIVE STUDY AT A SOCIAL SERVICE CENTER IN BANDUNG - Ridho Rinaldi; Yuliyantini (International Journal of Cultural and Social Science, 2026)
This study examines the practice of social work supervision in a Social Service Center in Bandung, Indonesia. Supervision is an essential component of professional social work practice that supports service quality, professional development, and workers’ well-being. However, supervision within institutional settings often faces structural and managerial challenges. This study employed a qualitative descriptive approach using semi-structured interviews with five social workers selected through purposive sampling. The findings show that supervision practices consist of administrative, educational, and supportive functions, although administrative supervision tends to dominate. Ethical principles such as confidentiality, professionalism, and trust are widely understood but have not been fully institutionalized within formal supervisory mechanisms. Supervisory dilemmas arise from power relations, institutional policy pressures, and limited resources. Despite these constraints, supervision contributes positively to improving professionalism, emotional resilience, and service quality. The study highlights the need for a more structured, reflective, and supportive supervision system in Indonesian social service institutions.